Clinical Nurses’ Knowledge and Attitude on Palliative Care: A Cross-Sectional Study - Nepal, Parbati; Garbuja, Chandra Kumari; Nepal, Manju (Journal of Lumbini Medical College, 2021)
Introduction: Palliative care is a multidisciplinary approach for enhancing the quality of life of terminally ill patients. For nurses, being the core members of the palliative care team, adequate knowledge and a positive attitude are crucial. This study aimed to assess clinical nurses' knowledge and attitude on palliative care. Method: A cross-sectional descriptive study was conducted among 122 nurses. A simple random sampling technique was applied to select the sample. Internationally validated questionnaires-“The Palliative Care Quiz for Nursing” and “Frommelt Attitudes Toward Care of the Dying Scale” were used to assess knowledge and attitude. Data were analyzed using descriptive statistics and inferential statistics. Results: The mean age of participants was 25±5.42 years and a majority (70.5%) were staff nurses. None of the participants had ever received training or in-service education related to palliative care. Only 29.5% had a fair level of knowledge and, 28.7% had a good level of attitude towards palliative care. Pearson correlation test revealed a negligible correlation between the level of knowledge and attitude (r= 0.135, p=0.887). Ethnicity (p=0.02) and religion (p=0.02) were statistically significant with the level of knowledge and care for dying relatives (p=0.03) was statistically significant with the level of attitude. Conclusion: The study revealed that nurses’ have poor knowledge of palliative care but had a fair attitude. As nurses are core members, regular training and in-service education can enhance their knowledge level. Positive reinforcement, appreciation, and reward for desirable behavior can help them develop a good attitude towards palliative care.